RADIOTHERAPY IN MANAGEMENT OF BRCA-POSITIVE OVARIAN CANCER - T. V. Gorodnova; S. B. Baranov; L. N. Shevkunov; S. A. Tyatkov; A. P. Sokolenko; C. B. Kotiv; E. N. Imyanitov; I. V. Berlev (Сибирский онкологический журнал, 2017)
Cancer cells with the loss of BRCA 1 or BRCA 2 function are unable to repair DNA double-strand breaks and demonstrate the increased sensitivity to various DNA-damaging agents. We aimed to describe successful treatment outcomes in two patients with BRCA1-associated ovarian cancer, who showed a complete clinical response to radiotherapy in combination with platinum-based chemotherapy. The progression-free survival was 11 months in one case and 8 months in another case.